Kontribusi Kekuatan Otot Lengan, Otot Perut, Otot Punggung Dan Fleksibilitas Punggung Pada Waktu Yang Dilakukan Dalam Bantingan Pundak Team Gulat Putera Puslatda Pon Jawa Timur - Bayu Nugraha Murdiansyah (CV. Multi Kreasi Media, 2022)
In its development in Indonesia, wrestling has been known by the public since pre-history. According to reliable sources, wrestling is also an original sport from Indonesia, although abroad it has existed and has grown since the golden age of ancient Greece and Rome. This wrestling sport has traditionally been known by the people of Indonesia, and currently the sport of wrestling is under the auspices of the Indonesian Whole Wrestling Association Organization (PGSI). Wrestling is a game of power struggles that bind themselves to each other and the other tries to beat or overthrow. The ability to perform good technique is a supporting factor in wrestling, including slamming. The slam is one of the important factors for adding points or points in wrestling and the shoulder slam is very often used in all championships. Therefore, in this study, researchers wanted to examine the contribution of arm muscle strength, abdominal muscle strength, back muscle strength and back flexibility at the time of shoulder slamming. This study aims to obtain information or data about the contribution between arm muscle strength, abdominal muscle strength, back muscle strength and back flexibility with respect to time in shoulder slamming. In this study, descriptive and associative research was used, namely by testing the men's wrestling team at Puslatda Pon East Java, which was taken as many as 20 wrestlers. From the regression analysis and multiple correlations, it was found that: the magnitude of the multiple correlation coefficient (R) between the arm muscle strength variable (X1), abdominal muscle strength variable (X2), back muscle strength variable (X3) and back flexibility variable (x4) together 56.66% can be explained by the variables of arm muscle strength, abdominal muscle strength, back muscle strength and back flexibility. While the rest is influenced by other factors that are not included in this analysis. The results of the F test calculation state that the calculated F value is 4.9016 and the F table is 3.06. In accordance with the criteria that the calculated F value = 4.9016 is greater than F Table = 3.06, it can be said that the multiple correlation coefficient (R) is significant.